2022
DOI: 10.1093/jamiaopen/ooac004
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing cancer prevention and survivorship care with a videoconferencing model for continuing education: a mixed-methods study to identify barriers and incentives to participation

Abstract: Objective To enhance cancer prevention and survivorship care by local health care providers, a school of public health introduced an innovative telelearning continuing education program using the Extension for Community Healthcare Outcomes (ECHO) model. In ECHO’s hub and spoke structure, synchronous videoconferencing connects frontline health professionals at various locations (“spokes”) with experts at the facilitation center (“hub”). Sessions include experts’ didactic presentations and case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 22 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…Two of the studies identified were related to the Extension for Community Healthcare Outcome (ECHO) model which involved connecting the health workers at spoke sites with experts at the hub using videoconferencing [ 27 , 28 ]. These studies aimed to assess the educational outcomes of the programme and to gain a better understanding of the reasons individuals choose or decline to participate in the Cancer ECHO programme.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two of the studies identified were related to the Extension for Community Healthcare Outcome (ECHO) model which involved connecting the health workers at spoke sites with experts at the hub using videoconferencing [ 27 , 28 ]. These studies aimed to assess the educational outcomes of the programme and to gain a better understanding of the reasons individuals choose or decline to participate in the Cancer ECHO programme.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies followed a mixed methods approach [ 24 , 25 ], four were observational studies [ 23 , 27 , 28 ] and one was a prospective study [ 26 ]. Overall, the studies highlighted that technology can be used for capacity building, providing specialised care in remote areas, and to navigate patients to facilities for diagnosis and treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further in-depth investigation into the identified PCP participation issue is warranted before undertaking a full-scale effectiveness and scalability study. The barriers and incentives to PCPs’ participation were the focus of our prior study, which revealed desired adaptations to better meet PCPs’ needs [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The final questions asked interviewees to compare this program with other continuing medical education, identify barriers to attending, and suggest improvements. (For the full interview guide, see Milgrom et al [ 23 ]).…”
Section: Methodsmentioning
confidence: 99%